Insights into Population Origins of Neotropical Junonia (Lepidoptera: Nymphalidae: Nymphalinae) Based on Mitochondrial DNA. (15th May 2012) - Pfeiler, Edward; Johnson, Sarah; Markow, Therese A.
Abstract : Cytochrome c oxidase subunit I (COI) sequences were used to estimate demographic histories of populations of the buckeye butterfly Junonia genoveva (Cramer) from Costa Rica and Mexico. Previous studies have revealed significant structure between populations of J. genoveva from coastal regions of northwestern Mexico, which utilize black mangrove Avicennia germinans (Acanthaceae) as a larval host plant, and inland populations from Costa Rica that feed on different hosts in the families Acanthaceae and Verbenaceae. The Mexico population of J. genoveva reported on here is located near the Northern limit of black mangrove habitat on the Pacific coast of North America and is hypothesized to have been established by northward migrations and colonization from southern source populations. The mismatch distribution, Bayesian skyline analyses, and maximum likelihood analyses carried out in FLUCTUATE were used to estimate changes in female effective population size (N ef ) over time in the two populations. Differences found in COI haplotype diversity, present-day N ef, and the timing of population expansions are consistent with the hypothesis that the Mexico population of J. genoveva is the more recently evolved.